2016
DOI: 10.5812/iranjradiol.28209
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Extracranial Internal Carotid Artery Due to Balloon Guiding Catheter Resulting in Asymptomatic Internal Carotid Artery Occlusion

Abstract: Dissection of the internal carotid artery (ICA) is a rare condition that accounts for a significant proportion of ischemic strokes in young adults. Iatrogenic dissection as a complication of neurointerventional procedures is a traumatic dissection which has been reported relatively rare in the literature. In this report, a case of dissection of the ICA is reported that was caused by repetitive movement of the balloon guiding catheter during stent-assisted thrombectomy (SAT), resulting in occlusion of the ICA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In addition, there may be concerns for complications such as dissection related to distal navigation of the BGC into the distal cervical ICA. 12,13 The purpose of this study was to compare the impact of BGC locations in patients treated for anterior circulation acute ischemic stroke by mechanical thrombectomy.…”
mentioning
confidence: 99%
“…In addition, there may be concerns for complications such as dissection related to distal navigation of the BGC into the distal cervical ICA. 12,13 The purpose of this study was to compare the impact of BGC locations in patients treated for anterior circulation acute ischemic stroke by mechanical thrombectomy.…”
mentioning
confidence: 99%
“…An ICA dissection case has been reported that was caused by repetitive movement of the balloon guiding catheter during thrombectomy for acute ischemic stroke. 15) The balloon was not bale-shaped dilated but vascular traction was performed with the minimum necessary dilatation. In the present case, a balloon guiding catheter could be inserted into the origin of ICA, but if it can only be inserted into the common carotid artery, embolic protection devices during stent deployment are required.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the incidence of iatrogenic artery dissection during reperfusion therapy for acute cerebral infarction is relatively high (1.0%–3.9%). 4 , 5 , 9 , 15 , 16) Several reasons for this are as follows: a guidewire and catheter are guided to an occluded artery in the absence of a roadmap 9) ; a relatively thick guidewire and catheter are guided several times 9) ; stent retriever traction-related vascular injury 17 , 18) ; a guiding catheter with a balloon is used 11) ; excessive suction through a catheter for the purpose of thrombus aspiration 12) ; rotation of head and neck affects the shapes of extracranial blood vessels during reperfusion therapy under local anesthesia in most patients, making the use of a roadmap impossible; and early recanalization is goal, making guidewire/catheter operations relatively rough. Furthermore, 1.5% 2) and 16.7% 1) of patients with iatrogenic artery dissection during cerebral angiography or neuroendovascular treatment required stenting, respectively, whereas 44.4% 9) of patients with iatrogenic artery dissection during reperfusion therapy for acute cerebral infarction required it; the percentage was relatively high.…”
Section: Discussionmentioning
confidence: 99%